The life and theology of Bishop John Ponet (1516-1556) - Earngey, M (2018)
This thesis provides a major revision of the life and theology of Bishop John Ponet (1516-1556). Ponet was one of the most important English bishops within the mid-Tudor Church of England. However, he has been seriously neglected thanks to the paucity of scholarly attention given to his life and theology, and the tendency to minimise his contribution to the English reformation to political theology. This thesis corrects both the neglect and imbalance of Ponet studies through the retrieval of a substantial body of newly discovered sources, including thirty-six books owned and annotated by Ponet, over seven-hundred pages of manuscript material authored by Ponet, various letters relative to Ponet, and other archival material pertaining to Ponet. The introductory chapter of the thesis provides the historiographical context and methodological framework of the dissertation. Chapter one investigates Ponet’s upbringing in Kent and uncovers his intellectual, linguistic, astronomical, and dramatical contributions as a leading member of the ‘Athenian Tribe’ at Cambridge University. Chapter two surveys the period of Ponet’s archiepiscopal patronage under Henry VIII and progress during the early reign of Edward VI. It reveals the continuities between Ponet’s private convictions under Henry VIII and his public writings under Edward VI. Chapter three details Ponet’s episcopal accomplishments and demonstrates his transition from evangelical theologian to one of the most important figures among English bishops, alongside Archbishop Cranmer and Bishop Ridley. Chapter four examines Ponet’s reaction to the accession of Queen Mary and his subsequent exile, elucidating Ponet’s role as superintendent of the Strassburg exiles. Chapter five provides the theological counterpart to the previous chapter, and illuminates Ponet’s thought concerning clerical marriage, political theology, and sacramental theology. This dissertation contributes the most detailed account of Ponet’s life to date and presents the most comprehensive survey of his theological thought within the history of reformation scholarship.